Effect of staged intervention on adherence, anaemia, heart function, and pro-inflammatory factors in chronic kidney diseases haemodialysis patients - Wan, Deheng; Sun, Jiakang; Guo, Fei; Wang, Yan (Journal of the Pakistan Medical Association, 2026)
Objective: To analyse the effects of staged intervention on adherence, anaemia, cardiac function and pro-inflammatory factors in chronic kidney disease patients undergoing haemodialysis. Method: The retrospective study was conducted at Qinhuangdao Haigang Hospital, China, and comprised data from January to December 2023 of chronic kidney disease patients undergoing dialysis treatment. The patients were divided into two cohorts based on intervention methods. Those in control group A received routine intervention, while those in observation group B were given intervention with changes at different stages. Comparisons were made with respect to treatment adherence, anaemia, heart function and pro-inflammatory factors. Data was analysed using SPSS 20. Results: Of the 100 patients, 50(50%) were in group A; 25(50%) males and 25(50%) females. The mean age was 53.20±8.25 years. Group B had 50(50%) patients; 26(52%) males and 24(48%) females. The mean age was 53.85±8.40 years (p>0.05). Treatment adherence of group B was higher than that of group A (p<0.05). After the intervention, group B had higher levels of haemoglobin, albumin, haematocrit, cardiac index score, stroke volume and left ventricular ejection fraction (p<0.05), but lower C-reactive protein, procalcitonin and interleukin-6 levels (p<0.05) than group A. Conclusion: Staged interventions could improve treatment adherence, alleviate anaemia symptoms, enhance heart function, and reduce the levels of pro-inflammatory factors in individuals with chronic kidney disease undergoing dialysis treatment. Key Words: Staged intervention, Chronic kidney disease, Haemodialysis, Adherence, Heart function, Pro-Inflammatory factors.